Polymer composite reinforced with nanoparticles produced from graphitic carbon-rich fly ash. (August 2017) - Algarni, Abdullah; Salah, Numan; Bourchak, Mostefa; Jilani, Asim; Alshahrie, Ahmed; Nahas, Mahmoud Nadim
Carbon nanotubes and graphene are considered effective reinforcement materials for various polymers because of their superior properties. However, they are expensive and difficult to separate and incorporate individually into matrix systems because of their tendency to exist in clustered form. In this work, carbon nanoparticles produced from graphitic carbon-rich fly ash by high-energy ball milling are evaluated as a reinforcement in a high-performance epoxy matrix system. They were used in various weight fractions ranging from 0.1 to 2 wt.%. The obtained carbon nanoparticles have an average particle size of around 20 nm, while XPS spectrum shows active carbonyl groups on their surfaces. The mechanical tensile properties of the carbon nanoparticles/epoxy nanocomposite, including their Young's modulus, stiffness, and load at fracture, were investigated. Moreover, the effect of ethanol as a dispersion medium was studied. The obtained results indicate that the Young's modulus and load at fracture changed only slightly upon the addition of carbon nanoparticles to the epoxy matrix system. On the other hand, the stiffness was improved by 60% over that of the pure epoxy matrix system. This improvement was obtained at 0.6 wt.% carbon nanoparticle content. The test results indicate that ethanol is effective in modifying the nanocomposite mechanical properties. Additionally, results show that low-cost CNPs might be useful as a reinforcement material for high-stiffness products.